Peningkatan Hasil Belajar PAK dan BP Melalui Pembelajaran Berbasis PBL Kelas 7 Fase D di SMP N 2 Tebing Tinggi - Erwita Emiliana Br Sembiring; Anselmus Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The low learning outcomes of students at SMP N 2 Tebing Tinggi in the subject of Catholic Religious Education and Character Building were caused by the monotonous teaching method, it’s the lecture method, which is lack variation. To solve this issue, the researcher applied the Project-Based Learning (PBL) method to improve student learning outcomes. The research question was whether the implementation of PBL can improve learning outcomes in Catholic Religious Education and Character Building. This study used the Classroom Action Research (CAR) method, conducted in two cycles. Each cycle consist of four stages: planning, implementation, observation, and reflection. The topic used in this research is "I Am a Unique Image of God." The instruments used included learning outcome tests (pre-test and post-test) and observation sheets to monitor the students’ engagement during the learning process. The result shows a significant improvement in students' learning outcomes from the pre-test to the post-test after the implementation of PBL. In addition to enhancing students' understanding of the "Image of God" concept, PBL method also successfully to motivate students to actively participate in learning, particularly through projects that relevant to daily life.